A pilot-scale study of dynamic response scenarios for the flexible operation of post-combustion CO2 capture. (May 2016) - Tait, Paul; Buschle, Bill; Ausner, Ilja; Valluri, Prashant; Wehrli, Marc; Lucquiaud, Mathieu
Highlights: Five dynamic operating scenarios for CO2 capture are implemented at pilot scale. An online sensor provides continuous measurements of solvent CO2 loading. Solvent circulation times have a significant effect on dynamic plant response. Real-time solvent capacity could be an important variable for control systems. Full plant operating data are provided with the electronic version of the paper. Abstract: The ability to operate flexibly is critical for the future implementation of carbon capture and storage (CCS) in thermal power plants. A dynamic test campaign examines the response of a CO2 absorption/desorption pilot-scale plant to realistic changes in flue gas flow rates and steam supply, representative of the operation of a Natural gas combined cycle (NGCC) plant fitted with post-combustion capture. Five scenarios, demonstrating the operational flexibility that is likely to be encountered in an energy market with significant penetration from intermittent renewables, are presented, with 30% monoethanolamine (MEA) as the absorbing solvent. It complements a wider effort on dynamic modelling of these systems where a lack of dynamic plant data has been reported. The campaign focuses on analysing critical plant parameters of the response of the pilot plant to a gas turbine shutdown, a gas turbine startup and three enhanced operational flexibility scenarios, including two for power output maximisation and one for frequency response with a rapid increase of steam supply to the reboiler. The campaign also demonstrates the use of continuous in situ solvent lean loading measurement with the use of a novel online continuous liquid sensor. It confirms that no significant barriers to flexible operation of amine post-combustion capture are found, although there remains scope for the improvement of plant response. Solvent inventory and circulation times are found to have a significant effect on capture rate during certain dynamic operations. A large solvent inventory increases total circulation times, which can result in additional time being required for the plant to return to steady state following a perturbation. The plant is forced to operate with a non-optimal capture rate while the solvent loading at the absorber inlet stabilises is identified as a potential impact. Use of interim solvent storage and continuous online measurement of solvent CO2 loading, combined with comprehensive knowledge of liquid circulation times and potential mixing effects, are suggested as methods for improving plant response to dynamic operation, thereby increasing CCS plant flexibility.